IbM Bank Sampah Desa Mojorejo Kota Batu - Novi Puji Lestari; Dicky Wisnu Usdek Riyanto (STKIP Andi Matappa, 2018)
The population is Mojorejo Batu residents, who are mostly housewives and small entrepreneurs who generate a lot of waste both plastic waste and wet waste each day. During this time residents Mojorejo waste management assisted by PKK villagers who walked less maximal. The purpose of this activity is to help citizens Mojorejo to utilize plastic waste into products that can be sold and helpful.The main activity of this service program is processing plastic waste into salable goods or recycling of the product, so that it can increase income mothers Mojorejo villagers. For this is still low awareness of the public about the impact of the use of goods that cause waste to the environment. The method used is to provide training to mothers resident Mojorejo to utilize plastic waste into a product worthy of sell.